Liquid helium as a filling medium in superconducting microwave systems; Soviet Technical Physics Letters; Vol. 10, № 6 - Artemenko S. N. Sergey Nikolaevich; Kaminsky V. L. Valery Ludvigovich; Samoilenko (Samoylenko) G. M. Gennady Mikhailovich; Yushkov Y. G. Yuri Georgievich (1984, 1984)
В фонде НТБ ТПУ отсутствует